International politics & state strength - Volgy, Thomas J. (Lynne Rienner Publishers, 2003)
Practicing agnosticism around passionate believers; Who cares? the salience and contours of global architecture; The three faces of State strength; Assessing State strength among the major powers; "Creeping Incrementalism" and Group Hegemony" : State strength and the New World order; Gazing through the crystal ball: the stability of today's architecture; What if: Another round of architectural enhancements for a New World order.